2017 IEEE/ACM 39th International Conference on Software Engineering Companion (ICSE-C) 2017
DOI: 10.1109/icse-c.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

Helping Programmers Improve the Energy Efficiency of Source Code

Abstract: This paper briefly proposes a technique to detect energy inefficient fragments in the source code of a software system. Test cases are executed to obtain energy consumption measurements, and a statistical method, based on spectrum-based fault localization, is introduced to relate energy consumption to the system's source code. The result of our technique is an energy ranking of source code fragments pointing developers to possible energy leaks in their code.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Other studies aimed at a more extensive energy consumption analysis, by comparing the energy efficiency of similar programs in specific usage scenarios [4,17], or by providing conclusions on the energy impact of different implementation decisions [7]. Several other works have shown that several factors, such as different design patterns [22,31], coding practices [21,26,29,32], and data structures [15,23,24,27], actually have a significant influence in the software's energy efficiency.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies aimed at a more extensive energy consumption analysis, by comparing the energy efficiency of similar programs in specific usage scenarios [4,17], or by providing conclusions on the energy impact of different implementation decisions [7]. Several other works have shown that several factors, such as different design patterns [22,31], coding practices [21,26,29,32], and data structures [15,23,24,27], actually have a significant influence in the software's energy efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…In fact, this is a recent and intensive area of research where several techniques to analyze and optimize the energy consumption of software systems are being developed. Such techniques already provide knowledge on the energy efficiency of data structures [15,27] and android language [25], the energy impact of different programming practices both in mobile [18,22,31] and desktop applications [26,32], the energy efficiency of applications within the same scope [2,17], or even on how to predict energy consumption in several software systems [4,14], among several other works.…”
mentioning
confidence: 99%
“…The research which relate the closest to our study are the ones of Pereira et al [31,32]. In their studies, a tool under development named SPELL is presented.…”
Section: Related Workmentioning
confidence: 88%
“…Additionally, our approach does not rely on the coefficient of test case similarity, but instead evenly distributes the energy consumption among the items covered by the test cases. While the goal of the SPELL tool [31,32] lies in providing the means to precisely locate energy hotspots in source code, our study aims to investigate if more naive approaches can be used to effectively locate them. This enables us to lie the groundwork to accurately understand through empirical experimentation the magnitude of the tradeoff that lies between performance and precision of spectrum based energy hotspot localization.…”
Section: Related Workmentioning
confidence: 99%
“…Apigee's survey on the reasons leading to bad mobile app reviews: https://cloud.google.com/apigee/news (visited on September 10, 2019) 2. High Risk Android Apps: https://www.verizonwireless.com/ support/services-and-apps/ (visited on September 10, 2019) 3. Tap is a gesture in which a user taps the screen with his finger.…”
Section: Introductionmentioning
confidence: 99%